Extending Viability of Bifidobacterium longum in Chitosan-Coated Alginate Microcapsules Using Emulsification and Internal Gelation Encapsulation Technology - Ji, Rui; Wu, Jiahui; Zhang, Junliang; Wang, Tao; Zhang, Xudong; Shao, Lei; Chen, Daijie; Wang, Jian (Frontiers in Microbiology, 2019)
Bifidobacteria are considered one of the most important intestinal probiotics because of their significant health impact. However, due to gastrointestinal fluid sensitivity, a number of supplementary Bifidobacteria are unable to survive passage through the gastrointestinal tract, severely limiting their ability to confer health benefits to the host. Emulsification and internal gelation are an encapsulation technique with great potential for probiotic protection during storage and the gastrointestinal transit process. This study prepared microcapsules using an emulsification and internal gelation encapsulation method with sodium alginate, chitosan, and Bifidobacterium longum as wall material, coating material, experimental strain, respectively. Optical, scanning electron, and focal microscopes were used to observe the microcapsule surface morphology and internal viable cell distribution, and a laser particle size analyser and zeta potentiometer were used to evaluate the chitosan coating characteristics. In addition, microcapsule probiotic viability after storage, heat treatment, and simulated gastrointestinal fluid treatment were examined. Alginate microcapsules and chitosan-coated alginate microcapsules both had balling properties and uniform bacterial distribution. The latter kept its balling properties after freeze-drying, verified by SEM, and had a clear external coating, observed by optical microscope. The particle size of chitosan-coated alginate microcapsules was slightly larger than the uncoated microcapsules. The zeta potential of alginate and chitosan-coated alginate microcapsules was negative and positive, respectively. Heat, acid and bile salt tolerance, and stability tests revealed that the decrease of viable cells in the chitosan-coated alginate microcapsule group was significantly lower than in uncoated microcapsules. These experimental results indicate that the chitosan-coated alginate microcapsules protect B. longum from gastro-intestinal fluid and high temperature conditions.